The imaginary - Harrold, A. F. 1975- (Bloomsbury, 2015)
Rudger, an imaginary playmate, must find his friend Amanda before he fades away to nothing, while eluding the only other person who can see him, evil Mr. Bunting, who hunts--and possibly even eats--imaginaries.